2018
DOI: 10.1186/s12877-018-0778-3
|View full text |Cite
|
Sign up to set email alerts
|

No one size fits all—the development of a theory-driven intervention to increase in-hospital mobility: the “WALK-FOR” study

Abstract: BackgroundThere is growing evidence that mobility interventions can increase in-hospital mobility and prevent hospitalization-associated functional decline among older adults. However, implementing such interventions is challenging, mainly due to site-specific constraints and limited resources. The Systems Engineering Initiative for Patient Safety (SEIPS 2.0) model has the potential to guide a sustainable, site-tailored mobility intervention. Thus, the aim of the current study is to demonstrate an adaptation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
88
1
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(94 citation statements)
references
References 26 publications
1
88
1
4
Order By: Relevance
“…Successful multicomponent programs in acute care have often invested in careful identification of local barriers and enablers to shape interventions. 11,12 In acute care, these have generally focused on staff knowledge, patient and family awareness, and clearer communication of goals within teams and with patients. Our findings in the rehabilitation setting suggest that positive and consistent communication about mobility expectations within teams and with patients and families are also essential and that effective symptom management, flexible routines, meaningful activities and active engagement of families may be important additional strategies to consider.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful multicomponent programs in acute care have often invested in careful identification of local barriers and enablers to shape interventions. 11,12 In acute care, these have generally focused on staff knowledge, patient and family awareness, and clearer communication of goals within teams and with patients. Our findings in the rehabilitation setting suggest that positive and consistent communication about mobility expectations within teams and with patients and families are also essential and that effective symptom management, flexible routines, meaningful activities and active engagement of families may be important additional strategies to consider.…”
Section: Discussionmentioning
confidence: 99%
“…Patient, staff and organisational barriers to greater mobilisation have been explored within acute hospital settings. [9][10][11][12][13] However, these barriers may be different in rehabilitation settings where case-mix, staff training, patient and staff expectations, routines and resourcing may differ from acute care wards. We therefore undertook a mixed methods observational study to describe and understand mobility in rehabilitation patients, to inform local improvement strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Existing perceptions of patient and family resistance need to be clarified by engaging patients and families and seeking their perspectives on barriers and opportunities for improving mobility, to develop patient-centred solutions. Overall barriers 35 (11) 34 (9) 33 (12) .77 33 (9) 35 (12) .39 Knowledge 25 (17) 23 (20) 22 (13) .86 19 (15) 28 (20) .04…”
Section: Discussionmentioning
confidence: 99%
“…Distributing surveys through staff meetings meant not all eligible staff may have received a survey (eg staff on leave or night shift) and the true denominator is uncertain. The survey only considers staff perceptions and should be considered in the context of measures of actual mobility performance and patient perceptions 9,10,13 ; our findings from these linked studies are reported elsewhere in this journal.…”
mentioning
confidence: 99%
“…Implementation of interventions in clinical practice is challenging since it is affected by factors on organizational, professional, intervention and patient level (Chaudoir, Dugan, & Barr, 2013). Previous studies have developed mapping guides addressing factors for implementing in hospital physical activity interventions including knowledge, attitudes and barriers as perceived by various healthcare providers and patients (Moore et al, 2014;Zisberg et al, 2018). Moore et al (2014) concentrated on barriers to behaviour change using the "capability, opportunity, motivationbehaviour (COM-B) system."…”
Section: Backg Rou N Dmentioning
confidence: 99%